Children's everyday manifestations of grief and grieving in early childhood education and care. Issue 11 (18th August 2022) - Quiñones, Gloria; Lipponen, Lasse; Pursi, Annukka; Barnes, Melissa
ABSTRACT: This article investigates children's everyday manifestations of grief and grieving situations. Medical and psychological approaches to grief and grieving usually focus on the death of loved ones. It is argued that everyday grief and grieving in early childhood education and care (ECEC) is present in social situations where loneliness and withdrawal are experienced by children. A cultural–historical approach was used to examine everyday grief and grieving in the preschool setting. Video observations were made of Mayra, a 5-year-old girl living in a rural Mexican community. The findings show that grief and grieving are affected by children's social situations, the material conditions of the location and the adult's role in compassionate approach in alleviating grief. Implications from this study highlight the need to examine everyday situations where children experience loneliness and withdrawal when relating to peers as a part of children's larger frame of grief.